Valoración de la salud periodontal de piezas pilares en pacientes portadores de PPR que asistan al centro de atención odontológico de la Universidad de las Américas - Hinojosa Campoverde, Cesar Andrés (2019)
Currently, a large part of society is a carrier of some type of dental prosthesis being more used: partial removable prosthesis for its ease of preparation and cost for the patient, plus a third of the adult population from 40 years onwards has a removable partial denture. One of the main disadvantages is this type of rehabilitation. Thus, a study was conducted on 30 patients who attended the Dental Care Center of the University of the Americas to assess the periodontal health of the abutment teeth where the removable partial denture is found, by perioontal probing and by means of a survey with which you will analyze the patient's hygiene habits as well as the teeth in the mouth as well as the care of the prosthesis. Objective: To assess the periodontal health of the abutment teeth where the removable partial denture is found by the periodontogram. Materials and Methods: Materials used for research The equipment used for diagnosis, the explorer and the periodontal probe, the north, a survey with questions on patient hygiene, as well as oral oral therapy. The correct use of prosthetic hygiene. Result: It was obtained that 100 percent of the patients were related to periodontal disease, in addition to the patients did not use dental floss and mouth rinses and a minimal part of the universe sanitized as their removable partial denture.